Ischemic and Hemorrhagic Stroke Among Critically Ill Patients With Coronavirus Disease 2019: An International Multicenter Coronavirus Disease 2019 Critical Care Consortium Study*. Issue 12 (December 2021) - Cho, Sung-Min; Premraj, Lavienraj; Fanning, Jonathon; Huth, Samuel; Barnett, Adrian; Whitman, Glenn; Arora, Rakesh C.; Battaglini, Denise; Porto, Diego Bastos; Choi, HuiMahn; Suen, Jacky; Bassi, Gianluigi Li; et al.
Abstract : OBJECTIVES: Stroke has been reported in observational series as a frequent complication of coronavirus disease 2019, but more information is needed regarding stroke prevalence and outcomes. We explored the prevalence and outcomes of acute stroke in an international cohort of patients with coronavirus disease 2019 who required ICU admission. DESIGN: Retrospective analysis of prospectively collected database. SETTING: A registry of coronavirus disease 2019 patients admitted to ICUs at over 370 international sites was reviewed for patients diagnosed with acute stroke during their stay. PATIENTS: Patients older than 18 years old with acute coronavirus disease 2019 infection in ICU. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Of 2, 699 patients identified (median age 59 yr; male 65%), 59 (2.2%) experienced acute stroke: 0.7% ischemic, 1.0% hemorrhagic, and 0.5% unspecified type. Systemic anticoagulant use was not associated with any stroke type. The frequency of diabetes, hypertension, and smoking was higher in patients with ischemic stroke than in stroke-free and hemorrhagic stroke patients. Extracorporeal membrane oxygenation support was more common among patients with hemorrhagic (56%) and ischemic stroke (16%) than in those without stroke (10%). Extracorporeal membrane oxygenation patients had higher cumulative 90-day probabilities of hemorrhagic (relative risk = 10.5) and ischemic stroke (relative risk = 1.7) versus nonextracorporeal membrane oxygenation patients. Hemorrhagic stroke increased the hazard of death (hazard ratio = 2.74), but ischemic stroke did not—similar to the effects of these stroke types seen in noncoronavirus disease 2019 ICU patients. CONCLUSIONS: In an international registry of ICU patients with coronavirus disease 2019, stroke was infrequent. Hemorrhagic stroke, but not ischemic stroke, was associated with increased mortality. Further, both hemorrhagic stroke and ischemic stroke were associated with traditional vascular risk factors. Extracorporeal membrane oxygenation use was strongly associated with both stroke and death. Abstract : Supplemental Digital Content is available in the text.